2010
DOI: 10.1007/s10006-010-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the alar base width of patients submitted to surgically assisted maxillary expansion

Abstract: SAME procedure increased the alar base width even performing the alar bases sutures; however, despite the widening of 1.6 mm, the clinical result was not compromised and better than without the technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 17 publications
0
37
0
8
Order By: Relevance
“…2 The best results in the treatment of skeletally mature individuals have been achieved using SARPE, 3 whereas nonsurgically assisted rapid maxillary expansion (NSARPE) in these individuals has been associated with complications, such as buccal tilt and displacement of the teeth that anchor the expander. [4][5][6][7] SARPE techniques and variations have been described elsewhere, [2][3][4][5][6][7][8][9][10][11][12] and studies have confirmed that the activation of the tooth-borne (Hyrax) or tooth-tissue-borne (Haas) expanders after osteotomies dissipates tensions responsible for the lateral movement of the maxilla and all adjacent structures, such as the teeth and the bones of the face and skull, [13][14][15] which affects the nasal cavity, 16 nasal septum, 17 lateral walls and floor of the nose 18 and nasal area, 19 as well as the upper lip, 20 alar base, 21 gingiva, 22 and facial soft tissues. 23 This study used finite element analysis (FEA) to evaluate the distribution of tensions in the anchor teeth of a tooth-tissueborne expander when different types of osteotomies were simulated.…”
mentioning
confidence: 99%
“…2 The best results in the treatment of skeletally mature individuals have been achieved using SARPE, 3 whereas nonsurgically assisted rapid maxillary expansion (NSARPE) in these individuals has been associated with complications, such as buccal tilt and displacement of the teeth that anchor the expander. [4][5][6][7] SARPE techniques and variations have been described elsewhere, [2][3][4][5][6][7][8][9][10][11][12] and studies have confirmed that the activation of the tooth-borne (Hyrax) or tooth-tissue-borne (Haas) expanders after osteotomies dissipates tensions responsible for the lateral movement of the maxilla and all adjacent structures, such as the teeth and the bones of the face and skull, [13][14][15] which affects the nasal cavity, 16 nasal septum, 17 lateral walls and floor of the nose 18 and nasal area, 19 as well as the upper lip, 20 alar base, 21 gingiva, 22 and facial soft tissues. 23 This study used finite element analysis (FEA) to evaluate the distribution of tensions in the anchor teeth of a tooth-tissueborne expander when different types of osteotomies were simulated.…”
mentioning
confidence: 99%
“…Os efeitos da EMCA não se fazem sentir somente sobre os dentes, ossos e respiração nasal dos indivíduos com MTD, pois existem efeitos também sobre os tecidos moles nasais (BERGER et al 1999), lábio superior (NARY FILHO et al 2002), tecidos moles faciais (RAMIERI et al 2008;KILIÇ et al 2008) e largura da base alar (ASSIS, DUARTE & GONÇALES, 2010).…”
Section: Palatino (Figura 8)unclassified
“…However other structures, organs and systems related to bones involved may be affected, causing problems in positioning of teeth, dental arches, masticatory function, phonation, swallowing, temporomandibular joints, breathing and facial aesthetics 1 . Transverse maxillary deficiency (TMD) is characterized by posterior uni or bilateral crossbite, crowded and rotated teeth, as well as high palate 2,3 .…”
Section: Introductionmentioning
confidence: 99%